APPLICATION OF THE PRINCIPLE OF HUMANITY IN THE CREATION OF AN OPTIMAL MODEL OF CRIMINAL SANCTIONS (Prima Journal of Integrated Studies, 2026)
This article analyzes the role and importance of the principle of humanity in the formation of an optimal model of criminal law sanctions. The issues of proportionality, sparing of repression, individualization of punishment, and taking into account the level of social danger of a crime in the formation of criminal law sanctions are scientifically covered. The need to classify crimes according to their social danger, distinguish between intentional and negligent crimes is also substantiated. The importance of taking into account the nature of the crime, the harm caused, the form of guilt, and the characteristics of the guilty person when determining sanctions is emphasized. The article shows the need to expand alternative punishment measures, increase judicial discretion, and strengthen the preventive function of punishment in the formation of an optimal model of sanctions. On this basis, scientific conclusions are formulated aimed at humanizing and improving criminal legislation.
Keywords: Criminal law sanctions, determination of punishment, lower and upper limits of punishment, categories of crime, criminalization of the act, ideal model of sanction, crime policy, individualization of punishment.